CARS diagnostics of near-critical fluid in small mesopores - Arakcheev, V.G.; Bagratashvili, V.N.; Morozov, V.B. (ALT Proceedings, 2026)
Due to the high spacial resolution and theinterference nature, coherent anti-Stokes Ramanscattering (CARS) spectroscopy is well suited forthe diagnostics of composites based on transparentnanoporous hosts. In particular, the adsorption of afluid on the walls of nanopores and the formation ofa condensed phase in their volume leads to obvioustransformation of the CARS spectra. Recently wehave developed a model which describes thebehavior of molecular spectra at isothermalcompression in cylindrical nanopores. Calculationsbased on the model have shown a good agreementwith the experimental results for carbon dioxide innanoporous glass with pores of diameter of severalnanometers. Here we use the developed approach toinvestigate the phase behavior of carbon dioxide inglass nanopores at near-critical temperatures. It hasbeen experimentally shown that condensation innanopores occurs at relatively low pressures atsubcritical and even at supercritical temperatures.The analysis based on the developed model allowsto reveal some qualitative and quantitativecharacterizations of the shift of critical point.